Comparison of measured photon and electron beam dose distributions between 3D water phanton and profiler 2 scanning system, South Africa - Moji, Kabelo McDonald (University of Limpopo (Medunsa Campus), 2014)
Background and Objectives: To establish whether the profiler 2 scanning system can be used as a substitute for the 3D-water phantom, by comparing the percentage depth doses and beam profiles for both the photons and electron beams, and validating the results using CMS XiO treatment planning system. Methods: Beam data (profiles, percentage depth doses and absolute dosimetry) were acquired for the two systems: (3D-water phantom and profiler 2 scanning system) for beam energies 6 MV and 15 MV photon beams, and 4, 6, 8, 10, 12 and 15 MeV electron beams generated by the Elekta Synergy linear accelerator (linac) for the field sizes of 6 × 6 cm2, 10 × 10 cm2, 14 × 14 cm2, 20 × 20 cm2, and 25 × 25 cm2 at depths of 0.5 cm, 1.0 cm, 2.0 cm, and 5.0 cm respectively. These measurements were acquired using ionization chambers in water and diode detectors in Perspex. The acquired data was sent to CMS XiO treatment planning system for validation. Results: In general, the dose distributions for both systems compared very well with uncertainties within recommended limits. The largest maximum difference in symmetry was 1.6 % for a 6 MV photon beam defined at 25 × 25 cm2 field size. The largest maximum difference in flatness was 2.77 % for a 4 MeV electron beam defined at 10 × 10 cm2 applicator size. The penumbra largest maximum difference was 1.708 cm for 8 MeV electron beam defined at 25 × 25 cm2 applicator size, which was outside the recommended limit of 1.2 cm. The largest maximum difference in field size was 2.388 cm for a 6 MeV electron beam defined at 20 × 20 cm2 applicator size, which was outside the recommended limit of 0.4 cm. The largest maximum difference in percentage depth dose at 10 cm depth was 1.69 % for the 6 MV photon beam. The absolute dose output measurements showed a very good agreement between the two systems to a maximum percentage difference and highest standard deviation of -0.99 % and 0.69 % respectively for the 6 MV photon beam. Validation measurements showed an agreement to less than 1 % and 2 mm for percentage depth doses and beam profiles respectively. Conclusion and recommendation: From the results obtained, it is evident that the profiler 2 scanning system can be used as a substitute for the 3D-water phantom beam data acquisitions during linear accelerator commissioning. The future work based on this study could be to study the limitations involved with the profiler 2 scanning system when used during measurements for commissioning of a linear accelerator. Limitations like field size (maximum field size of 20 × 30 cm2 at SSD = 100 cm), number of Perspex slabs to be used on top of the profiler 2 scanning system and diagonal profile measurements.
Thesis ( MSc ( Physics) ) -- University of Limpopo, 2013.
Keywords: Photons.